Mobile devices on teaching-learning process for high school level - Suryasa, Wayan (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the study is to describe the main characteristics and use of mobile technology as a fundamental element in the construction of knowledge, with the use of technologies the possibilities of interacting with students and teachers are increased without the obligation of physical presence, improving communication between high school students. In today's society in continuous growth, technological progress appears to give clear answers to computer advances and communications. That is why today mobile technologies appear giving way to a new social, cultural and educational model. The article creates theoretical conceptualizations in the use of mobile devices in high school, the current impact on the practice of these terminals in regular education at the Baccalaureate levels.The devices are really becoming tools available to teachers and students in order to improve their teaching practices, consult, research and access information from anywhere on the planet at any time in all sectors of society.